Apoptotic Effect of Galbanic Acid via Activation of Caspases and Inhibition of Mcl‐1 in H460 Non‐Small Lung Carcinoma Cells. (6th March 2015) - Oh, Bum‐Seok; Shin, Eun Ah; Jung, Ji Hoon; Jung, Deok‐Beom; Kim, Bonglee; Shim, Bum Sang; Yazdi, Mahsa Chitsazian; Iranshahi, Mehrdad; Kim, Sung‐Hoon
<x xml:space="preserve">Abstract</x> Galbanic acid (GBA), a major compound of Ferula assafoetida, was known to have cytotoxic, anti‐angiogenic and apoptotic effects in prostate cancer and murine Lewis lung cancer cells; the underling apoptotic mechanism of GBA still remains unclear so far. Thus, in the present study, the apoptotic mechanism of GBA was investigated mainly in H460 non‐small cell lung carcinoma (NSCLC) cells because H460 cells were most susceptible to GBA than A549, PC‐9 and HCC827 NSCLC cells. Galbanic acid showed cytotoxicity in wild EGFR type H460 and A549 cells better than other mutant type PC‐9 and HCC827 NSCLC cells. Also, GBA significantly increased the number of Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) positive cells and sub G1 population in H460 cells. Western blotting revealed that GBA cleaved poly (ADP‐ribose) polymerase (PARP), activated Bax and caspase 9, attenuated the expression of Bcl‐2, Bcl‐xL, and Myeloid cell leukemia 1 (Mcl‐1) in H460 cells. However, interestingly, overexpression of Mcl‐1 blocked the ability of GBA to exert cytotoxicity, activate caspase9 and Bax, cleave PARP, and increase sub G1 accumulation in H460 cells. Overall, these findings suggest that GBA induces apoptosis in H460 cells via caspase activation and Mcl‐1 inhibition in H460 cells as a potent anticancer agent for NSCLC treatment. Copyright © 2015 John Wiley & Sons, Ltd.